Controlled Study of the Impact of a Virtual Program to Reduce Stigma Among University Students Toward People With Mental Disorders - Rodríguez-Rivas, Matías E.; Cangas, Adolfo J.; Fuentes-Olavarría, Daniela (Frontiers in Psychiatry, 2021)
Stigma towards mental disorders is one of today's most pressing global issues. The Covid-19 pandemic has exacerbated the barriers to social inclusion faced by individuals with mental disorders. Concurrently, stigma reduction interventions, especially those aimed at university students, have been more difficult to implement given social distancing and campus closures. As a result, alternative delivery for programs contributing to stigma reduction is required, such as online implementation. This paper reports the results of a controlled study focused on an online multi-component program on reducing stigma towards mental illness that included project-based learning, clinical simulations with standardized patients and E-Contact with real patients. A total of 40 undergraduate students from the Universidad del Desarrollo in Santiago, Chile, participated in the study. They were randomly divided between an intervention and control group. The intervention group participated in the online multi-component program, while the control group participated in an online educational program on cardiovascular health. We assessed the impact of the program by using the validated Spanish-language versions of the Attribution Questionnaire AQ-27 and the Questionnaire on Student Attitudes toward Schizophrenia with both groups, before and after the intervention. In addition, an ad hoc Likert scale ranging from 0 to 5 was used with the intervention group in order to assess the learning strategies implemented. Following the intervention, the participants belonging to the intervention group displayed significantly lower levels of stereotypes, perception of dangerousness, and global score towards people with schizophrenia (p<0.001). In addition, participants presented lower levels of dangerousness-fear, avoidance, coercion, lack of solidarity, and global score (p<0.001). The control group displayed no statistically significant differences in the level of stigma before and after the evaluation, for all of the items assessed. Finally, the overall assessment of each of the components of the program was highly positive. In conclusion, the study shows that online programs can contribute to reducing stigma towards mental disorders. The program assessed in this study had a positive impact on all the dimensions of stigma and all of the components of the program itself were positively evaluated by the participants.